Effects of Clostridium butyricum, Sodium Butyrate, and Butyric Acid Glycerides on the Reproductive Performance, Egg Quality, Intestinal Health, and Offspring Performance of Yellow-Feathered Breeder Hens - Wang, Yibing; Wang, Yang; Lin, Xiajing; Gou, Zhongyong; Fan, Qiuli; Jiang, Shouqun (Frontiers in Microbiology, 2021)
Butyrate has been reported to promote the performance and growth of chickens. The specific roles and efficacy of different sources of butyrate remain unclear. Thus, the present study aimed to investigate and compare the effects of Clostridium butyricum (CB), sodium butyrate (SB) and butyric acid glycerides (tributyrin, BAG) on the reproductive performance, egg quality, intestinal health and offspring performance of yellow-feathered chickens. A total of 300 Lingnan yellow-feathered broiler breeders were assigned to 5 treatment groups: control (CL), 1×108 CFU/kg CB (CBL), 1×109 CFU/kg CB (CBH), SB and BAG. Results showed that the laying performance and egg quality were increased by CBL, CBH and BAG. Both CB treatments increased the hatchability of fertilized eggs. Maternal supplementation with both levels of CB significantly elevated the growth performance of offspring. Treatment with CBL, CBH, SB and BAG all improved the oviduct-related indices and reduced the plasmal antioxidant variables. The CBH, CBL and BAG treatments also improved the intestinal morphology to different degrees. Jejunal contents of IL-6 were decreased by CBH and BAG, while those of IL-4, IL-6, IL-1β and IgY were decreased by SB. Transcripts of nutrient transporters in jejunal mucosa were also up-regulated by CBH, CBL and SB treatments and expression of. Bcl-2 associated X protein (BAX) was decreased by CBL, CBH and BAG. In cecal contents, CBL increased Firmicutes and Bacillus, while CBH decreased the abundance of Proteobacteria. Also, the co-occurrence networks of intestinal microbes were regulated by CBH and BAG. In conclusion, dietary inclusion of CB and BAG improved reproductive indices, egg quality and intestinal morphology of breeders. CB also influenced the hatching performance of breeders and growth performance of the offspring while SB improved the oviduct-related indices. These beneficial effects may result from the regulation of cytokines, nutrient transporters, apoptosis, and gut microbiota; high-level CB had more obvious impact. Further study is needed to explore and understand the correlation between the altered gut microbiota induced by butyrate and the performance, egg quality, intestinal health as well as offspring performance.